Application of docking method to assess the activity of hydrocarbonoclastic bacteria (HCB) from marine origin in bioremediation process - Ariyanti Suhita Dewi (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
Hydrocarbons are one of the main sources of acute and chronic stressors in marine environmentthat are potentially damaging the ecosystem if not properly overcame. As an attempt to restore theenvironment, microbial degradation is a logical solution owing to its low cost and environmentalfriendliness. Screening of microbes with bioremediation activities can be performed in vitrobymeans of high throughput screening (HTS) and/or in silicovia docking method. The latter haspractical advantages over the first in terms of time and cost. In this review, the use of virtualscreening is demonstrated to analyse the specificity of cytochrome-c peroxidase (CCP) enzymefrom hydrocarbonoclastic bacteria Marinobacter hydrocarbonoclasticus. Result showed thatCCP is a decent receptor for simple aromatic hydrocarbons. Despite previous reports on thealkane degradation activities of M. hydrocarbonoclasticus, this result demonstrates a newperspective on its potential to bioremediate low molecular weight polycyclic aromatic hydrocarbon(PAH) with moderate activity.